2016
DOI: 10.1111/1750-3841.13216
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Digestion: Multiscale Processes of Food Digestion

Abstract: Food digestion is a complex, multiscale process that has recently become of interest to the food industry due to the developing links between food and health or disease. Food digestion can be studied by using either in vitro or in vivo models, each having certain advantages or disadvantages. The recent interest in food digestion has resulted in a large number of studies in this area, yet few have provided an in-depth, quantitative description of digestion processes. To provide a framework to develop these quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 95 publications
(130 reference statements)
0
50
0
Order By: Relevance
“…It is known that SBC ≥5 is considered adequate; i.e., it meets the organism's physiological needs. 21 The present study observed that the values from all groups were suitable (greater than 5); therefore, although a lower SBC value could be observed in the E2 group, as compared with groups C and E1, this most likely does not interfere in the saliva's buffering action.…”
Section: Discussionmentioning
confidence: 46%
“…It is known that SBC ≥5 is considered adequate; i.e., it meets the organism's physiological needs. 21 The present study observed that the values from all groups were suitable (greater than 5); therefore, although a lower SBC value could be observed in the E2 group, as compared with groups C and E1, this most likely does not interfere in the saliva's buffering action.…”
Section: Discussionmentioning
confidence: 46%
“…As a simple way of modelling the enzymatic hydrolysis, we introduce random bond cleavage to the model. We do this by introducing a rate constant k break that the bond between any two beads is broken at each streaming step; if a bond is cleaved, the two beads participating in it are no longer connected via the harmonic potential (1). All bonds are equally susceptible to attack: this mode of enzyme degradation of carbohydrates is known as a multichain attack in the literature [25,26].…”
Section: Polymer Modelmentioning
confidence: 99%
“…It is noteworthy, however, that the kinetics of in vitro salivary‐gastric starch digestion has been investigated and, when modeled (Bhattarai et al., ; Bustos, Vignola, Pérez, & León, ; Tamura et al., ), yielded parameters (for example, rate of digestion and maximum digestible starch) of importance in the analysis of the GIT by in vitro techniques. Bornhorst, Gouseti, Wickham, and Bakalis () additionally clarified the usefulness of salivary‐gastric digestion in engineering, modeling, and understanding digestion, including starch digestion.…”
Section: Starch Digestionmentioning
confidence: 99%
“…This possibly indicates that structural and/or feed material component changes in the samples during the passage through the pig GIT prevented complete digestion of some starchy materials, assuming that the residence time in the pig GIT was long enough in the study to approximate an infinite time. The pig GIT has been used as an in vivo replica of the human GIT (Bornhorst et al., ), and the presence of undigested or incompletely digested starch in the pigs’ samples could be a pointer to not always assume full digestibility ( D ∞ is 100 g/100 g dry starch) of starchy materials, irrespective of material or processing, when modeling starch digestograms (Liu & Sopade, ). For computational versatility as further discussed below, therefore, maximum digestible starch, D ∞ , is better assumed to be less than or equal to 100 g/100 g dry starch to serve all modeling scenarios instead of being restrictive.…”
Section: Modeling Starch Digestogramsmentioning
confidence: 99%